Politics and morality through the lens of sallust’s bellum catilinae (2017)
Sallust, with apparent sense of moral obligation wrote Bellum Catalinae (Catiline War) as it were, to relieve his experience of corruption and bribery in politics during the Roman Republic. Interpretably, the work has another thrust: the place of morality in politics. This article features how, particularly through characterization of Catiline, a politician's desire for supremacy is presented as borne out of his innate self-serving disposition and hardly any incline of morality, love of country or self-sacrifice. By profiling some of the associates of Catiline in his conspiracy, the paper also indicates how moral decay made ambition to excel for personal advancement supersede genuine interest in the good of the commonwealth. Attention is further drawn to how loyalty, duty discipline was eroded with the lure of luxury, women wine. The paper notes that the debauched Sallust's Catiline got recruits for his revolt, not only from among the embittered disadvantaged lowly citizens, but also from models of moral scourge which beset his society among the nobility. This paper concludes that Sallust, through Bellum Catalinae, depicts how a state can become endangered by politicians who are morally debased